Military Neurosurgery: A Range of Service Options. Issue 6 (June 2016) - Menger, Richard P.; Wolf, Michael E.; Lang, Richard W.; Smith, Donald R.; Nanda, Anil; Letarte, Peter; Rosner, Michael K.
Abstract : The pathway to military neurosurgical practice can include a number of accession options. This article is an objective comparison of fiscal, tangible, and intangible benefits provided through different military neurosurgery career paths. Neurosurgeons may train through active duty, reserve, or civilian pathways. These modalities were evaluated on the basis of economic data during residency and the initial 3 years afterwards. When available, military base pay, basic allowance for housing and subsistence, variable special pay, board certified pay, incentive pay, multiyear special pay, reserve drill pay, civilian salary, income tax, and other tax incentives were analyzed using publically available data. Civilians had lower residency pay, higher starting salaries, increased taxes, malpractice insurance cost, and increased overhead. Active duty service saw higher residency pay, lower starting salary, tax incentives, increased benefits, and almost no associated overhead including malpractice coverage. Reserve service saw a combination of civilian benefits with supplementation of reserve drill pay in return for weekend drill and the possibility of deployment and activation. Being a neurosurgeon in the military is extremely rewarding. From a financial perspective, ignoring intangibles, this article shows most entry pathways with initially modest differences between the cumulative salaries of active duty and civilian career paths and with higher overall compensation available from the reserve service option. These pathways become increasingly discrepant over time as civilian pay greatly exceeds that of military neurosurgeons. We hope that those curious about or considering serving in the United States military benefit from our accounting and review of these comparative paths. ABBREVIATIONS: FAP, Financial Assistance Program NADDS, Navy Active Duty Delay for Specialists TMS, Training in Medical Specialties